How does firm strategy affect the relationship between entrepreneurial strategic orientation and firm growth? A preliminary analysis on small and medium size hotels in peninsular Malaysia - Kasim, Azilah; Altinay, Levent (2016)
This paper presents a preliminary analysis on how firm strategy (FS) affects the relationship between entrepreneurial strategic orientation and firm growth within the context of small and medium size hotels in Peninsular Malaysia.The hypotheses were tested using 254 completed questionnaires from hotel representatives at managerial level.Regression analysis results showed that the hypothesis on positive effect of entrepreneurial orientation (EO) on growth of small and medium size hotels could not be accepted.On the other hand, the hypothesis on the moderating effect of FS on the relationship between EO and growth of small and medium size hotels was confirmed. Based on the findings, several implications are proposed.